In-silico and biochemical analysis of ethyl acetate fraction of Olax subscorpioidea leaf on DMBA-induced cell proliferation in female rats - Ayodeji Adebayo Adelegan; Titilayo Omolara Johnson; Titilope Modupe Dokunmu; Emeka Eze Joshua Iweala (Journal of HerbMed Pharmacology)
Introduction: Olax subscorpioidea is a medicinal plant that Africans use to treat numerous ailments, including cancer. This research examines the antioxidant, anticancer, and in-silico properties of ethyl acetate fraction of Olax subscorpioidea’s (OSEA) on 7,12-Dimethylbenz(α) anthracene (DMBA)-induced cell proliferation in female rats. Methods: Forty female Sprague Dawley rats averaging 110 ± 20 g were induced proliferation with DMBA (80 mg/kg) and treated with ethyl acetate fraction (250 mg/kg BW) of O. subscorpioidea or tamoxifen (6.6 mg/kg BW) before and after induction. The trial lasted 22 weeks. In-vivo antioxidant parameters such as superoxide dismutase (SOD), malondialdehyde (MDA), and reduced glutathione (GSH) were examined. Likewise, carcinoma antigen marker (CA153), and DNA methyltransferase 3-like (DNMT3L) activity were measured. Gas chromatography-mass spectrometry (GC-MS) detected the bioactive compounds, and molecular docking studies predicted the mechanism of action of OSEA against DNA methyltransferase. Results: Treatment with OSEA significantly increased the SOD activity, enhanced GSH levels, and lowered the levels of MDA, CA-153, and DNMT3L in DMBA-exposed rats. The GC-MS analysis of OSEA revealed the presence of 40 bioactive compounds. The molecular docking revealed that 4-cyclopentene-1,3-dione (-6.407 kcal/mol), 2-(2-hydroxyethylthio) (-4.926 kcal/mol) and 3,4,5,6-tetrahydrophthalic anhydride (-6.16 kcal/mol) had the lowest binding energies against DNMT1, DNMT3A, and DNMT3B, respectively. 2-(2-hydroxyethylthio) was the least toxic. The molecular dynamic simulation revealed that the interaction between DNMT3A and 2-(2-hydroxyethylthio) propionic was stable to an extent. : The in-silico and biochemical analysis of the ethyl acetate fraction of O. subscorpioidea showed that it can protect against lipid peroxidation and oxidative stress and may be a potent source of drug that serves as an effective therapeutic in the future.